The GmFWL1 (FW2‐2‐like) nodulation gene encodes a plasma membrane microdomain‐associated protein. (27th April 2017) - Qiao, Zhenzhen; Brechenmacher, Laurent; Smith, Benjamin; Strout, Gregory W.; Mangin, William; Taylor, Christopher; Russell, Scott D.; Stacey, Gary; Libault, Marc
Abstract: The soybean gene Gm FWL1 ( FW2‐2‐like1 ) belongs to a plant‐specific family that includes the tomato FW2‐2 and the maize CNR1 genes, two regulators of plant development. In soybean, Gm FWL1 is specifically expressed in root hair cells in response to rhizobia and in nodules. Silencing of Gm FWL1 expression significantly reduced nodule numbers supporting its role during soybean nodulation. While the biological role of Gm FWL1 has been described, its molecular function and, more generally, the molecular function of plant FW2‐2‐like proteins is unknown. In this study, we characterized the role of GmFWL1 as a membrane microdomain‐associated protein. Specifically, using biochemical, molecular and cellular methods, our data show that GmFWL1 interacts with various proteins associated with membrane microdomains such as remorin, prohibitins and flotillins. Additionally, comparative genomics revealed that GmFWL1 interacts with GmFLOT2/4 (FLOTILLIN2/4), the soybean ortholog to Medicago truncatula FLOTILLIN4, a major regulator of the M. truncatula nodulation process. We also observed that, similarly to MtFLOT4 and GmFLOT2/4, GmFWL1 was localized at the tip of the soybean root hair cells in response to rhizobial inoculation supporting the early function of GmFWL1 in the rhizobium infection process. Abstract : This manuscript focuses on describing the molecular function of GmFWL1, a tomato FW2‐2 (LeFW2‐2) soybean homolog that was previously shown to control soybean nodulation. Here, using biochemical and microscopic methods, we demonstrate that GmFWL1 is interacting with well‐characterized plasma membrane microdomain‐associated proteins. Interestingly, reinforcing the role of membrane microdomains in regulating legume nodulation, GmFWL1 proteins are translocated to the tip of the root hair cell in response to rhizobial inoculation; aggregation previously noticed when observing the root hair localization of the Medicago truncatula FLOT2, a microdomains‐associated protein also regulating the nodulation process. Together, these results reveal for the first time the cellular function of an FWL protein and support a role of microdomain‐associated proteins during the early event of the nodulation process.